Cinnamomum verum J. S. Presl (Lauraceae): padronização de processos extrativos e viabilidade de bioprodutos leishmanicidas - KZAM, Pollyanna Melo (2022)
Leishmaniasis are prevalent and neglected infectious-parasitic diseases that affect public health, especially in developing countries, and parasite resistance to current therapeutic regimens is also proven, making it necessary to research new drugs. In this sense, natural resources, especially those of plant origin, make an effective contribution to obtaining new bioactives; demanding the development of validation studies of the species, with emphasis on the standardization of extractives; with emphasis on those obtained from species of wide popular use. This work aimed to carry out a literature review of studies carried out with Cinnamomum verum J. S. Presl. (Lauraceaee), a species of wide occurrence in Brazil, with wide and diversified popular use; and develop a study of standardization of extracts from its leaves, based on chemical, physical-chemical and biological tests (leishmanicidal activity and in vitro cytotoxicity). Chapter 1 is titled: “Cinnamomum verum J. S. Presl (Lauraceae): a review of biotechnological potential” and chapter 2 presents the study of standardization of Cinnamomum verum leaves. In the patterning study, leaves of plant material were collected in a natural habitat in São Luís, Maranhão, Brazil; submitted to botanical identification, drying, milling and extraction in 70% ethanol, by factorial design (23 ); using as independent variables: extractive procedures (membrane with ultrasound-MU, extraction in a Soxhlet-S apparatus and percolation-P) and hydromodule ratio (1:6, 1:8 and 1:10); and as dependent variables: yield, total polyphenol content, flavonoid content and antioxidant activity (DPPH). Additionally, the 02 (two) extracts with the most expressive results were selected for analysis by Liquid Chromatography coupled to Diode Array, Liquid Chromatography coupled to Mass Spectrometry, in vitro analysis against promastigotes of Leishmania amazonensis and Leishmania infantum and cytotoxicity assay in RAW 264.7 cells. The P 1:10 extract showed the best yield (21.19%); polyphenols (257.947 ± 0.388 mg EAG/g), flavonoids (83.760 ± 0.053 mg EQ/g) and antioxidant activity (2.27 ± 0.19 µg/mL) showed more expressive results in MU 1:6, S 1:10 and P 1:8, respectively. The extracts S 1:10 and P 1:8 were active against promastigote forms of Leishmania amazonensis and Leishmania infantum, with more expressive results for the extract P 1:8, within 48 hours; but showed moderate toxicity (IS <10) on peritoneal macrophages (RAW 264.7) with significant differences between S 1:10 and P 1:8 extracts. In both extracts, phenolic compounds were identified: type A proanthocyanidin trimer, puerarin, rutin, epigallocatechin gallate, epigallocatechin gallate isomer and kaempferol-3-rhamnoside-7-rhamnoside. In view of these results, it can be inferred that the extractive procedure and hydromodule ratio interfere in obtaining extracts from cinnamon leaves, proven by the best results of the extracts obtained in a Soxhlet apparatus in the 1:10 hydromodule and percolation in the 1:8 hydromodule, thus allowing the standardization of the species; also showing potential leishmanicidal activity, which should encourage further studies.